Pemodelan Tingkat Kriminalitas di Provinsi Jawa Timur dengan Regresi Data Panel Spasial - Ni Komang Jeni Frika Yanti; Made Susilawati; Ni Luh Putu Suciptawati (Journal on Education, 2023)
Crime is any action or behavior that violates the law and is prohibited by the state and society. East Java is a province that ranks second after North Sumatra with a number of crimes above the average, reaching 11% of the total number of crimes in Indonesia. This shows that the level of security in East Java still needs to be improved in order to minimize crime rates and provide a sense of security to all people in East Java Province. The goal to be achieved in this study is to model and find out the factors that significantly influence the crime rate in East Java Province for the 2017-2021 period using spatial panel data regression analysis. This research shows that there is a spatial lag effect of the model, with the model chosen to model the crime rate in East Java Province is the spatial lag fixed time effect with an of 71.54%. Factors that significantly influence are the number of unemployed, population density, average length of schooling, total population.